High Thermal Inertia Zones on Ceres From Dawn Data. Issue 3 (28th February 2020) - Rognini, E.; Capria, M. T.; Tosi, F.; De Sanctis, M. C.; Ciarniello, M.; Longobardo, A.; Carrozzo, F. G.; Raponi, A.; Frigeri, A.; Palomba, E.; Fonte, S.; Giardino, M.; et al.
Abstract: Thermal inertia is a key information to quantify the physical status of a planetary surface. We derive the thermal inertia of the surface of Ceres using spatially resolved data from the Dawn mission. For each location, this quantity can be constrained by comparing theoretical and observed diurnal temperature profiles from retrieved temperatures. We calculated Ceres's surface theoretical temperatures with a thermophysical model that provides temperature as a function of thermal conductivity and roughness, and we determined the values of those parameters for which the best fit with the observed data is obtained. Our results suggest that the area of crater Haulani displays thermal inertia values (up to 130–140 J·m −2 ·s −½ ·K −1 ) substantially higher than the very low to low values (from 1–15 to 50–60 J·m −2 ·s −½ ·K −1 ) derived for the overall surface of Ceres. The results are more ambiguous for the bright faculae located in the floor of crater Occator. Plain Language Summary: We have calculated Ceres's surface temperatures and we have compared them with the observations. We have used new high‐resolution data provided by the Dawn/National Aeronautics and Space Administration mission, which was launched in 2007 with the aim of studying two of the largest bodies of the Main Belt: Vesta and Ceres. Our results suggest that the surface is made of fine‐grained material, according to previous analysis made by other authors by using other independent data and methods. We have also studied two particular areas of Ceres that shows peculiar properties (albedo and/or chemical/physical structure). Key Points: The thermal inertia of the surface of Ceres has been derived using spatially resolved data from the Dawn mission The Haulani crater appears to have a higher thermal inertia with respect to Ceres's average The average thermal inertia of the surface of Ceres appears to have low values (1–15 J·m −2 ·s −½ ·K −1 )